Analysis of Varying-PRI Spotlight SAR Data - Zhou, Zi-Xuan; Deng, Yunkai; Wang, Wei; Jia, Xiaoxue; Wang, Robert (IEEE transactions on geoscience and remote sensing, 2022)
For ultrahigh-resolution spaceborne spotlight synthetic aperture radar (SAR), the effective swath width is limited by the severe range migration. By adapting the pulse repetition interval (PRI) according to the change of the slant range, however, the range migration can be substantially reduced, which makes the varying-PRI spotlight mode an attractive solution for future spaceborne SAR missions. This study provides a complete preprocessing framework for the varying-PRI spotlight SAR data, by which data equivalent to uniform sampling can be obtained, so that traditional processing algorithms designed for data on a regular grid can then be applied. Furthermore, in response to the non-ideal focusing results of the spotlight data, an in-depth analysis of the effects of the SAR acquisition geometry and processing algorithms on the Doppler spectral distribution is presented. Finally, a varying transmitted pulse duration scheme is proposed to enhance the performance of the varying-PRI spotlight SAR system.